The relationship of active consideration of health outcomes and intertemporal preferences to choice process variables and nutrition: evidence from an experiment on food choice - Tuyizere, Olivier; Gustafson, Christopher R. (Frontiers in Behavioral Economics, 2023)
Introduction Understanding drivers of individuals' food choices is critical to be able to address the public health epidemic of obesity-related health problems. A robust literature documents relationships between intertemporal preferences and body mass index (BMI). However, work on cognition differentiates resource investment in decision-making, with processes frequently categorized as habitual (low investment) vs. model-based (high investment). Methods We integrate variables related to cognition with intertemporal preferences to examine how discount rates and active consideration of health impacts of foods faced during choice relate to the nutritional quality of foods selected. Results Our results show that participants who actively consider health outcomes choose products with significantly higher nutritional quality compared to those who do not consider the health impacts of choices, even while controlling for discount rates. We also find that participants with lower discount rates selected foods with higher nutritional quality compared to high discount-rate participants, corroborating previous literature. Further, we find that participants who actively considered health during the choice process spent significantly more time making choices, while discount rates did not predict differences in decision times, suggesting a role for habitual vs. model-based decisions. Discussion These findings suggest that active consideration of the health consequences during food choice is an important predictor of the nutritional quality of choices even while accounting for intertemporal preferences, which may provide new opportunities to intervene in the decision-making process.